BET 2: Diagnostic value of ultrasound in determining lateral ligament injury of the ankle. Issue 1 (11th January 2019) - Hayes, Russ; Callaghan, Michael
Abstract : A short cut review was carried out to establish whether diagnostic ultrasound can accurately diagnose integrity of the lateral ligament complex in comparison to MRI. Two studies were directly relevant to the question using the described search methodology. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. Despite the utility of ultrasound there is no certainty of its advantage over MRI for injuries of the anterior talofibular ligament.